Study of the Course of the Inferior Dental Canal in the Iraqis Population Using Cone Beam Computed Tomography - Omar Basheer Taha AL-Tekreeti1, Noor Sabah Irhayyim2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: The inferior alveolar nerve (IAN) is one of the most important vital structures found in the mandible, knowing the precise location of the mandibula canal is helpful to decrease the incidence and avoid the injury to the (MC). Material & Method:30 males & 30 females were selected from the data of the (CBCT) stored in the computer joined to the device and the measurements were taken as follow “ The first section in transaxial view after mental foramen, where the loop of mandibular canal is formed, was selected as point A and interludes of 10 mm were selected for subsequent measurements (respectively, points B,C,D). On these sections, the shortest linear distances (in mm) from the most lingual aspect of the canal to the outer lingual cortical plate of the mandible(L) and from the mandibular canal to the inferior border of mandibular body(I) were measured. Furthermore, the minimum distance between the buccal cortices and the mandibular canal(B) were evaluated” as in (Fig. 1). Using SPSS software Version 15 the data that had been obtained was analyzed. Results: The results had been showed that there is no significant difference in measurements were taken between males and females groups in the measurement of the distance of the inferior dental canal to the buccal cortical and in the measurement of the distance of the inferior dental canal to lingual cortical bone of the mandible , only in the measurement of the (IDC) to inferior border of the mandible there was a significant difference in only one point Conclusion: It can be concluded from this study that the information can be obtained by the (CBCT) about the location of the (MC) can helpful for the surgeons to avoid damage to (MC) throughout surgical procedures in the mandible , and those information can give good overview and conception for course of the (MC) through the mandible.